Peningkatan Kualitas Kurikuler Pembelajaran Materi Diniyah pada Pendidikan Formal Pesantren: Pengalaman Pesantren di Jawa Timur - Sholihuddin, Ahmad; Nidak, Khoiru (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
Many pesantrens integrate the local content of diniyah subjects into their formal institutions, including schools and madrasahs. This integration implies that the teaching of diniyah (Islamic religious subjects) materials must adhere to the standards of general subject instruction, as implemented in Pesantren Tebuireng, Jombang, East Java. Therefore, it is necessary to enhance pedagogical competencies through training and mentoring to improve educators' abilities in three main areas: (1) teaching methods, (2) preparation of teaching tools, and (3) test development. This activity employed the Community-Based Research (CBR) model, which encourages co-learning processes and capacity building. The results of this community service initiative show that: (1) in terms of teaching methods, there was an improvement through self-improvement supported by the role of subject teacher association (MGMP) for diniyah teachers and peer teaching activities; (2) in terms of teaching tools, there was progress in preparing standardized lesson plans (RPP); and (3) in terms of evaluation and assessment, process skills need to be honed to produce questions of proportional cognitive quality, both at Middle Order Thinking Skills (MOTS) and Higher Order Thinking Skills (HOTS) levels. Keywords: Pedagogical competence, Islamic religious subjects, Formal education, Pesantre Abstrak: Banyak pesantren mengintegrasikan muatan lokal mata pelajaran diniyah ke dalam lembaga formalnya, baik sekolah maupun madrasah. Integrasi ini membawa implikasi pada kewajiban pelaksanaan pembelajaran materi diniyah yang harus mengikuti ketentuan pembelajaran mata pelajaran umum, seperti yang diterapkan di Pesantren Tebuireng, Jombang, Jawa Timur. Oleh karena itu, diperlukan peningkatan kompetensi pedagogik melalui pelatihan dan pendampingan untuk meningkatkan kemampuan tenaga pendidik dalam tiga aspek utama: (1) metode pengajaran, (2) penyusunan perangkat pembelajaran, dan (3) penyusunan soal. Kegiatan ini menggunakan model Community-Based Research (CBR) dengan pendekatan yang mendorong terjadinya proses co-learning dan pengembangan kapasitas. Hasil pengabdian menunjukkan: (1) pada aspek metode pengajaran, terjadi peningkatan kemampuan melalui self-improvement yang didukung oleh peran Musyawarah Guru Mata Pelajaran (MGMP) guru diniyah dan kegiatan peer teaching; (2) pada aspek perangkat pembelajaran, terjadi peningkatan kemampuan dalam penyusunan kelengkapan perangkat Rencana Pelaksanaan Pembelajaran (RPP) yang terstandar; dan (3) pada aspek evaluasi dan penilaian, diperlukan keterampilan proses untuk menghasilkan soal dengan kualitas pemikiran yang proporsional, baik pada level Middle Order Thinking Skills (MOTS) maupun Higher Order Thinking Skills (HOTS). Kata kunci: Kompetensi pedagogik, Mata pelajaran diniyah, Pendidikan formal, Pesantren